An analysis of fertility, prolificacy, and weight gaining data in the preweaning period of two groups of Blackhead Persian sheep at Kiboko Range Research Station (Preliminary information) - Rakoczi, G. (1974)
An experiment was begun in April 1973 to compare the performances of two groups of Blackhead Persian sheep: Group “A” and Group “B”. All the females in Group “A” are being upgraded to Dorper; Group “B” remains pure Blackhead Persian. The lambing percentege of both Group “A” (86%) and Group “B”(60%) was low but the lambing percentage of group “B” was unusually low. There was a difference in lambing distribution between Blackhead Persian and Dorper cross Blackhead Persian sheep. The lambing period of group “B” (22 days) was unexpectedly shorter than that of group “A” (34 days). The pretupping weight of the twin-giving ewes was slightly higher than the pretupping weight of the single giving ewes. The birth weights of Group”A” and Group “B” were 2.6 kg and 2.8 kg, respectively. The daily weight gain of both groups during the suckling period was similar i.e. 144±24 and 148±28 for Group ”A” and Group “B”, respectively.